Impact of PGL-I seropositivity on the protective effect of BCG vaccination among leprosy contacts: a cohort study. - Nádia C Düppre (Public Library of Science (PLoS), 2012)
Background Contacts of leprosy patients are at increased risk of developing leprosy and need to be targeted for early diagnosis. Seropositivity to the phenolic glycolipid I (PGL-I) antigen of Mycobacterium leprae has been used to identify contacts who have an increased risk of developing leprosy. In the present study, we studied the effect of seropositivity in patient contacts, on the risk of developing leprosy, stratified by Bacille Calmette Guerin (BCG) vaccination after index case diagnosis. Methodology/principal findings Leprosy contacts were examined as part of the surveillance programme of the Oswaldo Cruz Institute Leprosy Outpatient Clinic in Rio de Janeiro. Demographic, social, epidemiological and clinical data were collected. The presence of IgM antibodies to PGL-I in sera and BCG vaccination status at the time of index case diagnosis were evaluated in 2,135 contacts. During follow-up, 60 (2.8%; 60/2,135) leprosy cases were diagnosed: 41 among the 1,793 PGL-I-negative contacts and 19 among the 342 PGL-I-positive contacts. Among PGL-I-positive contacts, BCG vaccination after index case diagnosis increased the adjusted rate of developing clinical manifestations of leprosy (Adjusted Rate Ratio (aRR) = 4.1; 95% CI: 1.8-8.2) compared with the PGL-I-positive unvaccinated contacts (aRR = 3.2; 95% CI: 1.2-8.1). The incidence density was highest during the first year of follow-up for the PGL-I-positive vaccinated contacts. However, all of those contacts developed PB leprosy, whereas most MB cases (4/6) occurred in PGL-I-positive unvaccinated contacts. Conclusion Contact examination combined with PGL-I testing and BCG vaccination remain important strategies for leprosy control. The finding that rates of leprosy cases were highest among seropositive contacts justifies targeting this specific group for close monitoring. Furthermore, it is recommended that PGL-I-positive contacts and contacts with a high familial bacteriological index, regardless of serological response, should be monitored. This group could be considered as a target for chemoprophylaxis.